Fewer seats, resilient frequencies: Impacts of large-scale high-speed rail liberalisation on air transport supply - Albalate, Daniel; Gragera, Albert; Suau-Sanchez, Pere (Elsevier, 2026)
This paper examines how the liberalisation of high-speed rail (HSR) services affects competing air transport supply in short-haul markets. While previous research has focused mainly on HSR infrastructure expansion, less is known about how opening HSR markets to new entrants reshapes intermodal competition. Using the large-scale liberalisation of Spanish HSR in 2021 as a quasi-natural experiment, we estimate its causal impact on airline supply across major domestic corridors. Our results show that liberalisation led to a significant reduction in airline seat capacity (around 10–16%), while flight frequencies remained broadly stable. Airlines adjusted mainly by deploying smaller aircraft rather than by cutting flights, indicating a reduction in capacity with limited effects on route connectivity. These findings provide new evidence on how liberalisation reshapes intermodal competition and highlight its relevance for policymakers considering market opening as a tool to strengthen rail competitiveness and influence airline market outcomes.
Part of the special issue: Competition and regulation of long-distance land passenger transport in Europe
Keywords: High-speed rail; Airlines; Liberalisation; Intermodal competition. Transportation; 35 Commerce, Management, Tourism and Services; 3509 Transportation, logistics and supply chains